Esteganografia em Páginas Web - Guimarães, Bruno Bastos; Barreto, Luciano Porto (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2008: Companion Proceedings of the 8th Brazilian Symposium on Information and Computational Systems SecurityDO - 10.5753/sbseg_estendido.2008.20910, 2008)
This article does not have an abstract.